ANALYSIS OF FACTORS AFFECTING THE SNACKING HABITS OF CLASS I STUDENTS AGAINST THE INCIDENCE OF ACUTE DIARRHEA IN SD NEGERI 105335 DELI SERDANG VEGETABLE GARDEN IN 2018 - BR BANGUN, AYU ANGGRAINI (Journal of Public Health for Tropical and Coastal Region, 2020)
Diarrhea is characterized by increased frequency of bowel movements> 3 times a day with changes in the consistency of stool with or without mucus or blood. This type of research is a cross-sectional survey research with an explanatory research method approach . Total population of 74 students . The results showed that there was a statistically significant relationship between attitudes toward acute diarrhea ( p = 0.024) OR was 4.601 . Trust in acute diarrhea ( p = 0.007) OR value was 2.544 . Availability of snacks for acute diarrhea ( p = 0.0 12 ) OR is 0.187 . Peer influence against acute diarrhea ( p = 0.0 13 ) OR value was 6.773 . The family's role in acute diarrhea ( p = 0.021 ) OR value is 3,900. Ak late but , t idak statistically significant relationship exists between the large pocket money against acute diarrhea ( p = 0, 466 ) and the role of the mass media against acute diarrhea ( p = 0 , 0869 ) . It is expected that the school and parents pay more attention to the children's snack habits.